Frequency stabilization of multiple lasers on a single medium-finesse cavity. (9th March 2018) - Han, Chengyin; Zhou, Min; Gao, Qi; Li, Shangyan; Zhang, Shuang; Qiao, Hao; Ai, Di; Zhang, Mengya; Lou, Ge; Luo, Limeng; Xu, Xinye
Abstract: We present a simple, compact, and robust frequency stabilization system of three lasers operating at 649, 759, and 770 nm, respectively. These lasers are applied in experiments on ytterbium optical lattice clocks, for which each laser needs to have a linewidth of a few hundred or tens of kilohertz while maintaining a favorable long-term stability. Here, a single medium-finesse cavity is adopted as the frequency reference and the standard Pound–Drever–Hall technique is used to stabilize the laser frequencies. Based on the independent phase modulation, multiple-laser locking is demonstrated without mutual intervention. The locked lasers are measured to have a linewidth of 100 kHz and the residual frequency drift is about 78.5 Hz s −1 . This kind of setup provides a construction that is much simpler than that in previous work.